Design of a solar dish Stirling cogeneration system: Application of a multi-objective optimization approach - Ferreira, Ana C. M. (2017)
Energy market consumption is expected to increase by 44% from 2006 to 2030, mostly because of the lifestyle standards evolution, and development of industries and economics. In addition, the variations of the fossil fuel prices and the increase in pollutant gas emissions have instigated the research on other types of power generation systems. From the available technologies, Stirling systems have demonstrated simplicity and reliability, which are the key parameters to develop a cost-effective energy system. The study aims the development of a methodology for the thermal-economic optimization, at the design stage, of micro-CHP systems based on Stirling engine technology, and combined with a renewable energy source, the solar energy. To properly size the system, a methodology is proposed to define the total annual thermal power duration curve of a reference residential building in the North of Portugal. The methodology accounts for both heating and the domestic hot water needs. The thermal-economic model was formulated as an non-linear optimization problem with non-linear constrains. Each component of the cycle is modelled using the energy balances of the first law of thermodynamics. It is also proposed an economic model that defines the purchase cost of each system component. The cost equations include thermodynamic variables that directly affect the component cost and performance. The model yields two non-linear objective functions: the minimization of the total investment cost and the maximization of the efficiency of the system. Numerical simulations were developed in MatLab programming language using evolutionary algorithms. The multi-objective optimization results were expressed by Pareto curves. The obtained curve disclosed several design possibilities for which the thermal efficiencies vary between 66.3% and 76.1% for an annualized investment costs fluctuating between 1250 €/year and 2675 €/year.